PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH SISWA DENGAN MENGGUNAKAN MODEL PROBLEM BASED LEARNING - Febrianti, Putri; Prihaswati, Martyana; Kumalaretna, Wahyu Ning Dewi (Litbang PWM Jawa Tengah, 2025)
This classroom action research aims to determine whether the implementation of the Problem Based Learning (PBL) learning model can enhance students' problem solving skills on the topic integral in class XII-10 of SHS 4 Semarang odd semester of the 2024/2025 academic year. This research was conducted in two cycles, encompassing four stages: planning, action, observation, and reflection. The subjects of this study were 36 students of class XII-10 of SHS 4 Semarang. Data were obtained through a problem solving ability test. Based on the research and analysis conducted, it was found that the implementation of the Problem Based Learning (PBL) model has a positive impact on improving the problem solving skills of students of class XII-10 of SHS 4 Semarang in the odd semester of the 2024/2025 academic year. This is evidenced by a significant improvement in problem solving skills between Cycle I and Cycle II. In the first cycle, the average score for problem solving skills reached 75.87, but in the second cycle, this average score increased to 87.50. Thus, the application of the Problem Based Learning (PBL) learning model can improve students' problem solving skills.